Does the preparation for intravenous administration affect the composition of heroin injections? A controlled laboratory study. (3rd May 2021) - Andersen, Jannike M.; Bogen, Inger Lise; Karinen, Ritva; Brochmann, Gerd Wenche; Mørland, Jørg; Vindenes, Vigdis; Boix, Fernando
Abstract: Aims: To study whether the preparation procedure, and its acidic and heating conditions, used by heroin users to prepare heroin for intravenous administration affects the final composition of the fluid to be injected. Methods: Samples from different seizures of illegal heroin provided by the Norwegian police were prepared by adding water and ascorbic acid before heating under controlled conditions in the laboratory. Further, three seizures were prepared with different amounts of ascorbic or citric acid relative to their diacetylmorphine content. Pure diacetylmorphine base or salt was also submitted to the procedure applying two different heating intensities. The seizures and the final product after preparation were analysed for diacetylmorphine, 6‐acetylmorphine and morphine using liquid chromatography with tandem mass spectrometry (LC‐MS‐MS). Results: After preparation, a decrease of 19.8% (25th and 75th percentiles = −29.2 and −15.3) in the initial diacetylmorphine content was observed. Both the 6‐acetylmorphine and morphine content increased but, due to their low content in the initial product, diacetylmorphine still represented 83.9% (25th and 75th percentiles = 77.3 and 88.0) of the sum of these three opioids in the final solution. The loss of water during preparation caused an increase in the concentration of diacetylmorphine, 6‐acetylmorphine and morphine, depending on the heating intensity applied. The content of these opioids was affected by the quantity and type of acid added in relation to the heroin purity and the level of diacetylmorphine dissolved being proportional to the amount of ascorbic acid, but not citric acid, in the sample with high heroin purity. Conclusions: Preparation of heroin for intravenous injection appears to change the amount or concentration of diacetylmorphine and its active metabolites, 6‐acetylmorphine and morphine in the final product, depending on heroin purity, amount and type of acid used or heating conditions. These circumstances can contribute to unintentional variations in the potency of the final injected solution, and therefore affect the outcome after injection.